Spatially-Coupled Constant-Weight Code for Random Access in Fast Fading Channels - Lu, Shuai; Zheng, Jianping (IEEE communications letters, 2025)
In this letter, we propose a novel signature code, spatially-coupled (SC) constant-weight (CW) code, for random access in fast fading channels. Concretely, first, the spatial coupling base matrix is constructed with coupling width ω and uniform coupling strength, and one CW mother code is partitioned into ω subcodes. Then, the SC-CW signature code matrix is obtained by replacing all the ω non-zero entries in each column of the base matrix with the ω subcodes. Taking the CW code constructed recently based on the on-off pattern of the binary subspace chirps as the mother code, the generated SC-CW code inherits the CW and low fading coherence properties of the mother code. Moreover, the recent SC generalized approximate message passing algorithm was utilized to identify the active users with tailored input and output denoising functions. Finally, simulation results show that the proposed SC-CW code can achieve better performance than the conventional CW code.